SAT0719-HPR "and suddenly you are a person at risk of developing rheumatoid arthritis!" different perspectives of individuals on predictive testing – results of an international qualitative interview study. (15th June 2017) - Mosor, E; Stoffer, M; Steiner, G; Raza, K; Stack, RJ; Simons, G; Falahee, M; Schett, G; Hueber, A; Engelbrecht, M; Smolen, J; Stamm, T
Abstract : Background: People at risk of developing rheumatoid arthritis (RA) may be candidates for interventions aimed at preventing RA development [1]. The identification of such "at risk" populations includes testing for genetic and other (e.g. autoantibody) biomarkers. However, little is known about the people's perspectives on these tests, how they react and cope when identified as being a person "at risk" and what their unmet needs are. Objectives: To expore the perceptions about RA and predictive testing and to understand the various reactions and coping strategies used when identified as being at risk of developing RA from the perspective of those directly concerned. Methods: As part of the EuroTEAM project, a qualitative interview study with people who were informed of being at risk of developing RA was conducted. An interview schedule was developed and pilot-tested. Interviews were audio-recorded, transcribed verbatim and analyzed using thematic analysis. Results: A total of 34 individuals (with rheumatoid factor and/or ACPA positive) already informed of being at risk of developing RA participated in the study, from Austria (n=15), Germany (n=15), and the UK (n=4). In Vienna, people who had been tested within an expanded health exam participated in this study. In Birmingham and Erlangen, people with arthralgia were recruited from the outpatient clinics. Analysis of the interview data revealed five overarching themes related to predictive testing in the context of RA (Figure). There were differences between the perceptions of althralgia patients and asymptomatic individuals. People suffering from pain were much more frightened and worried when informed of being at risk of developing RA. As a consequence, they modified their lives in a larger extent and had greater knowledge about RA than those without any symptoms who were rather surprised, kept calm and hardly changed their lifestyle after being tested positive. Allmost all participants in this study would appreciate precise predictive tests in the context of RA. However, more than half of them would refuse synovial biopsy (even if this could help quantify risk more accurately) or preventive medication. Recommendations for an improved procedure of predictive testing in the field of RA were given, which could promote uptake of preventive strategies. Conclusions: Participants showed large differences in views about predictive testing in the context of RA risk and offered specific suggestions that should be incorporated into service design and delivery in the context of future predictive testing programmes. These findings may also be relevant to prediction and prevention in the context of other diseases where multiple genetic risk factors interact with environmental risk factors to drive disease development. References: van Steenbergen, H.W., T.W. Huizinga, and A.H. van der Helm-van Mil, The preclinical phase of rheumatoid arthritis: what is acknowledged and what needs to be assessed? Arthritis Rheum, 2013. 65(9): p. 2219–32. Disclosure of Interest: None declared